El Niño 1992-93: Its influence on the reproductive biology of Tagelus dombeii - Ishiyama, Víctor (1998)
The El Niño 1992-93 phenomena incremented the number of matures males and females, and induced the spawning of Tagelus dombeii, due to the rise of the sea water temperature. The sex proportion was 1.2:1.0, (female:male). In the accelerated gametogenesis, we differentiated : oogonias and oocytes (previtelogenesis), ovocytes I (primary vitelogenesis) and ovocytes II (secondary vitelogenesis). The maturity scale, with high percentage of matures specimens and in spawning, and scarce immaturity and in development, were classificated in : non differentiated, immaturity, mature and spawn.